Preparing for the School Readiness of Early Childhood by Enhancing the Well-Being and Family Support - Saputri, Wenny Hikmah; Risnawati, Erna (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
School readiness during early childhood establishes the fundamental basis for prospective academic achievement, emphasizing the necessity for a comprehensive preparation that encompasses both mental and physical readiness. The current study examines the impact of child well-being and family support on school readiness among young learners. This Study used a correlational quantitative approach, the research involved 139 children between the ages of 4 and 7, along with their parents and 30 teachers selected through purposive sampling based on their socioeconomic status. The participants included 54.7% boys (n=76) and 45.3% girls (n=63) from families with varying income levels – low-income (25%), middle-income (29%), and upper-middle-income (46%). The results of the regression analysis indicated that both family support and child well-being have a significant influence on children's school readiness. Particularly, there is a notable positive association among all factors, a correlation between school readiness and child well-being at 42% (r = 0.420, p < 0.001), highlighting that higher levels of child well-being are linked to increased school readiness. Furthermore, family support exhibits a positive contribution to school readiness at 37% (r = 0.370, p < 0.001). The findings suggest that preparing children for school should extend beyond academic and motor skills development to include substantial psychological support, thus enhancing their ability to thrive in an academic environment. Keywords: early childhood, Emotion, Emotion regulation, parenting, happiness References: Atkins, R., Deatrick, J. A., Bocage, C., Huc, R., Aromolaran, D., Besseir, E., Hinckson, A., Joseph, M., Kim, D., Lagman, D., Gladsden, V. L., & Lipman, T. H. (2022). School Readiness and Social Determinants of Health: A Collaboration with Community Teachers and Parents. SSRN Electronic Journal. https://doi.org/10.2139/ssrn.4090268 Ayriza, Y., Setiawati, F. A., Nurhayati, S. R., Gumelar, S. R., & Sholeha, E. P. D. R. (2019). Does sleep quality serve as a mediator between well-being and academic achievement? Cakrawala Pendidikan, 38(1), 63–74. https://doi.org/10.21831/cp.v38i1.22181 Azra, A., Risnawati, E., Hermaini, B., Hendra, M., Kartikawati, E., Buana, U. M., & Terbuka, U. (2023). How family communication pattern affect a family ’ s capacity for resilience during covid-19 pandemic. 11(1), 117–137. Barnett, M. A., Paschall, K. W., Mastergeorge, A. M., Cutshaw, C. A., & Warren, S. M. (2020). Influences of Parent Engagement in Early Childhood Education Centers and the Home on Kindergarten School Readiness. Early Childhood Research Quarterly, 53, 260–273. https://doi.org/10.1016/j.ecresq.2020.05.005 Borualogo;, Ihsana Sabriani, F. C. (2020). Subjective Well-Being of Indonesian Children:A Perspective of Material Well-Being. ANIMA Indonesian Psychological Journal, 44–47. https://doi.org/10.1515/9783111634487-006 Borualogo, I. S., & Casas, F. (2022). The children’s worlds psychological well-being scale: Adaptation and fit in the Indonesian context. Cogent Psychology, 9(1), 1–17. https://doi.org/10.1080/23311908.2022.2053377 Cress, C. J., Synhorst, L., Epstein, M. H., & Allen, E. (2012). Confirmatory factor analysis of the preschool behavioral and emotional rating scale (PreBERS) with preschool children with disabilities. Assessment for Effective Intervention, 37(4), 203–211. https://doi.org/10.1177/1534508411433499 Cress, C., Lambert, M. C., & Epstein, M. H. (2016). Factor Analysis of the Preschool Behavioral and Emotional Rating Scale for Children in Head Start Programs. Journal of Psychoeducational Assessment, 34(5), 473–486. https://doi.org/10.1177/0734282915617630 Diener, E., & Ryan, K. (2009). Subjective Well-Being: A General Overview. South African Journal of Psychology, 39(4), 391–406. https://doi.org/10.1177/008124630903900402 El Zaatari, W., & Maalouf, I. (2022). How the Bronfenbrenner Bio-ecological System Theory Explains the Development of Students’ Sense of Belonging to School? SAGE Open, 12(4), 1–18. https://doi.org/10.1177/21582440221134089 Golshirazi, F., & Sadeghi, A. (2021). The Effect of Home-to-School Transition Program on Social-Emotional Readiness of Preschool Students. Journal of Counseling Research. https://doi.org/10.18502/qjcr.v20i77.6147 Gómez-Leal, R., Holzer, A. A., Bradley, C., Fernández-Berrocal, P., & Patti, J. (2022). The relationship between emotional intelligence and leadership in school leaders: a systematic review. Cambridge Journal of Education, 52(1), 1–21. https://doi.org/10.1080/0305764X.2021.1927987 Gregory, T., Dal Grande, E., Brushe, M., Engelhardt, D., Luddy, S., Guhn, M., Gadermann, A., Schonert-Reichl, K. A., & Brinkman, S. (2021). Associations between School Readiness and Student Wellbeing: A Six-Year Follow Up Study. Child Indicators Research, 14(1), 369–390. https://doi.org/10.1007/s12187-020-09760-6 Halimah, N., & Kawuryan, F. (2010). Kesiapan Memasuki Sekolah Dasar Pada Anak Yang Mengikuti Pendidikan Tk Dengan Yang Tidak Mengikuti Pendidikan Tk Di Kabupaten Kudus. Jurnal Psikologi Universitas Muria Kudus, I(1), 1–8. http://www.pustaka.unpad.ac.id Harrington, E. M., Trevino, S. D., Lopez, S., & Giuliani, N. R. (2020). Emotion regulation in early childhood: Implications for socioemotional and academic components of school readiness. Emotion (Washington, D.C.), 20(1), 48–53. https://doi.org/10.1037/emo0000667 Holzer, J., Bürger, S., Lüftenegger, M., & Schober, B. (2022). Revealing associations between students’ school-related well-being, achievement goals, and academic achievement. Learning and Individual Differences, 95(March), 102140. https://doi.org/10.1016/j.lindif.2022.102140 Hughes, C., White, N., Foley, S., & Devine, R. T. (2018). Family support and gains in school readiness: A longitudinal study. British Journal of Educational Psychology, 88(2), 284–299. https://doi.org/10.1111/bjep.12188 Jung, S., & Choi, N. (2020). Effect of Family Functioning on Preschoolers’ School Readiness: Mediating Effects of Mothers’ Affective Parenting and Preschoolers’ Self-regulation. Family and Environment Research, 58(1), 1–12. https://doi.org/10.6115/fer.2020.001 Kokkalia, G., Drigas, A., Economou, A., & Roussos, P. (2019). School readiness from kindergarten to primary school. International Journal of Emerging Technologies in Learning, 14(11), 4–18. https://doi.org/10.3991/IJET.V14I11.10090 Lazarus, R. S. (1991). Emotion and Adaptation. Oxford University Press. https://doi.org/10.2307/2075902 Lin, M. L., & Faldowski, R. A. (2023). The Relationship of Parent Support and Child Emotional Regulation to School Readiness. International Journal of Environmental Research and Public Health, 20(6). https://doi.org/10.3390/ijerph20064867 Lombardi, C. M. (2023). Early Maternal Employment And Children’s School Readiness: Changing Associations Over Time? Journal of Child and Family Studies, 32(4), 1032–1047. https://doi.org/10.1007/s10826-022-02357-3 Lombardi, C. M., & Dearing, E. (2021). Maternal Support of Children’s Math Learning in Associations Between Family Income and Math School Readiness. Child Development, 92(1). https://doi.org/10.1111/cdev.13436 Luby, J. L., Barch, D. M., Belden, A., Gaffrey, M. S., Tillman, R., Babb, C., Nishino, T., Suzuki, H., & Botteron, K. N. (2012). Maternal support in early childhood predicts larger hippocampal volumes at school age. Proceedings of the National Academy of Sciences of the United States of America, 109(8), 2854–2859. https://doi.org/10.1073/pnas.1118003109 Mariyati, L. I. (2017). Usia dan Jenis Kelamin dengan Kesiapan Masuk Sekolah Dasar. Prosiding Seminar Nasional Psikologi UMG, 095, 331–344. Mashar, R., & Pudji Astuti, F. (2022). Correlation between Parenting Skills, Children’s Emotional and Intelligence Quotient with School Readiness. JPUD - Jurnal Pendidikan Usia Dini, 16(2), 215–223. https://doi.org/10.21009/JPUD.162.02 Nurmaria, H., & Risnawati, E. (2022). The Relationship of Loneliness and Internet Addiction To Psychological Well-Being in Adolescents. Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 5(2), 509. https://doi.org/10.22441/biopsikososial.v5i2.14644 Rahmawati. (2018). Kesiapan sekolah merupakan kesiapan anak untuk memasuki sekolah . Di Indonesia istilah kesiapan sekolah lazim digunakan untuk merujuk kesiapan anak masuk Sekolah Dasar ( SD ), sebagai sekolah f. Jurnal Pendidikan Usia Dini,12(November), 201–210. http://journal.unj.ac.id/unj/index.php/jpud Risnawati, E., Meiliyandrie, L., Wardani, I., Saputra, A. H., Pramitasari, M., Mercu Buana, U., Pendidikan, J., & Dini, U. (2023). Theory of Mind, Roles, and the Development of Emotion Regulation in Early Childhood. 17(2), 1693–1602. https://doi.org/10.21009/JPUD.172.01 Risnawati Erna, Arisandi Alfida, D. R. (2019). Peran Religiusitas dan Psychological Well-Being terhadap Resiliensi Korban KDRT. Journal.Univpancasila.Ac.Id, 10(2), 67–77. http://journal.univpancasila.ac.id/index.php/mindset/article/view/836 Ryff, C. D. (1989). Happiness is everything, or is it? Explorations on the meaning of psychological well-being. Journal of Personality and Social Psychology, 57(6), 1069–1081. https://doi.org/10.1037/0022-3514.57.6.1069 Ryff, C. D., & Keyes, C. L. M. (1995). The Structure of Psychological Well-Being Revisited. Journal of Personality and Social Psychology, 69(4), 719–727. https://doi.org/10.1037/0022-3514.69.4.719 Seran, T. N., Haryono, & Anni, C. T. (2017). School Readiness: Readiness Children Seen from The Whole Aspect of Early Childhood Development Article Info. Journel of Primary Education, 6(3), 224–232. http://journal.unnes.ac.id/sju/index.php/jpe St. Laurent, C. W., Burkart, S., Andre, C., & Spencer, R. M. C. (2021). Physical Activity, Fitness, School Readiness, and Cognition in Early Childhood: A Systematic Review. Journal of Physical Activity and Health, 18(8), 1004–1013. https://doi.org/10.1123/jpah.2020-0844 Turner, K. M. T., Dittman, C. K., Rusby, J. C., & Lee, S. (2017). Parenting Support in an Early Childhood Learning Context. In M. R. Sanders & T. G. Mazzucchelli (Eds.), The Power of Positive Parenting (pp. 242–251). Oxford University Press. https://doi.org/10.1093/med-psych/9780190629069.003.0021